Hubungan antara Obesitas dengan Derajat Nyeri pada Penderita Osteoarthritis Lutut di RS Bina Sehat Jember (Relationship between Obesity and Degree of Pain in Knee Osteoarthritis Patients at Bina Sehat Hospital, Jember) - Rizka Kusumaningsih; Muhammad Hasan; Irawan Fajar Kusuma (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Osteoarthritis (OA) is an abnormality of cartilage which is marked by clinical and radiological changes. The location OA is mostly at knee joint. In this study, the relationship between Waist-Hip Ratio (WHR) and Body Mass Index (BMI) with the degree of pain in patients with knee OA was investigated, measured by the Visual Analogue Scale (VAS). The study was conducted at Bina Sehat Hospital, Jember. Fifty two samples were taken by purposive sampling with established criteria. The statistical analysis to measure the relationship between BMI and VAS showed p= 0.000, which means there is a significant correlation between BMI and degree of pain in patients with knee OA. While, the relationship between WHR and VAS in male showed p= 0,095, which means there is no significant relationship between WHR and degree of pain in male patienst with knee OA. Analysis of WHR relationship with VAS in female showed p= 0,002, which means that there is a significant association between WHR and degree of pain in female patients with knee OA. It can be concluded that excess of BMI and WHR can increase the pain in patients with knee OA. Keywords: Waist Circumference, Body Mass Index (BMI), Knee Osteoarthritis (OA)